Beyond the double helix: the multifaceted landscape of extracellular DNA in Staphylococcus aureus biofilms - Bowden, Lucy C.; Finlinson, Jenny; Jones, Brooklyn; Berges, Bradford K. (Frontiers in Cellular and Infection Microbiology, 2024)
Staphylococcus aureus forms biofilms consisting of cells embedded in a matrix made of proteins, polysaccharides, lipids, and extracellular DNA (eDNA). Biofilm-associated infections are difficult to treat and can promote antibiotic resistance, resulting in negative healthcare outcomes. eDNA within the matrix contributes to the stability, growth, and immune-evasive properties of S. aureus biofilms. eDNA is released by autolysis, which is mediated by murein hydrolases that access the cell wall via membrane pores formed by holin-like proteins. The eDNA content of S. aureus biofilms varies among individual strains and is influenced by environmental conditions, including the presence of antibiotics. eDNA plays an important role in biofilm development and structure by acting as an electrostatic net that facilitates protein-cell and cell-cell interactions. Because of eDNA’s structural importance in biofilms and its ubiquitous presence among S. aureus isolates, it is a potential target for therapeutics. Treatment of biofilms with DNase can eradicate or drastically reduce them in size. Additionally, antibodies that target DNABII proteins, which bind to and stabilize eDNA, can also disperse biofilms. This review discusses the recent literature on the release, structure, and function of eDNA in S. aureus biofilms, in addition to a discussion of potential avenues for targeting eDNA for biofilm eradication.